2010
DOI: 10.3722/cadaps.2010.297-308
|View full text |Cite
|
Sign up to set email alerts
|

Non-stationarization of the Typical Curves and its Extension to Surfaces

Abstract: It is known that if the degree of the typical plane Bézier curve is increased infinitely, the curve will converge to the logarithmic (equiangular) spiral. The logarithmic spiral is one of log-aesthetic curves and they are formulated by : the slope of the logarithmic curvature graph. In this paper we define the non-stationary typical Bézier curve by making the transition matrix of the typical Bézier curve non-stationary and dependent on each side of the control polyline and defining the transition matrix in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This paper proposed quasi-log-aesthetic curves in polynomial Bézier form using Taylor polynomials. We have shown that quasi-log-aesthetic curves are better approximation than the curves generated by discretization [6]. Because of the limitation of polynomial curves, quasi-log-aesthetic curves are not good approximations when log-aesthetic curves are close to circular arcs.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This paper proposed quasi-log-aesthetic curves in polynomial Bézier form using Taylor polynomials. We have shown that quasi-log-aesthetic curves are better approximation than the curves generated by discretization [6]. Because of the limitation of polynomial curves, quasi-log-aesthetic curves are not good approximations when log-aesthetic curves are close to circular arcs.…”
Section: Discussionmentioning
confidence: 95%
“…We compare quasi-log-aesthetic curves with Bézier curves generated by Miura's method [6] using logarithmic curvature graphs. Miura's method discretizes log-aesthetic curves, and then using the discretized equation, Bézier control points are placed on the curve either by a constant arc length or by a constant tangential angle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations